Biting the bullet: the role of hobbyist metal detecting within battlefield archaeology - Natasha Ferguson (Internet Archaeology, 2013)
In the UK battlefields are becoming more frequently associated with the label 'heritage at risk'. As the concept of battlefield and conflict archaeology has evolved, so too has the recognition that battlefields are dynamic, yet fragile, archaeological landscapes in need of protection. The tangible evidence of battle is primarily identified by distributions of artefacts held within the topsoil, such as lead projectiles, weapon fragments or buttons torn from clothing; debris strewn in the heat of battle. Much of the battlefield therefore remains as a faint footprint and, where it survives, may provide valuable information, if recorded accurately.